Evaluation of lighting levels in companies exploiting phosphoric rocks for the production of agro-industrial goods in the department of Huila - Victoria Bonilla, Reinaldo Alfredo (2020)
The purpose of this study is to evaluate the lighting levels in the working areas of mining companies involved in the exploitation of phosphoric rocks for the production of agro-industrial goods in the department of Huila. To this end, measurements will be made with a luxometer, considering the location of the factories, and the natural and artificial lights. These measurements will be performed to evaluate the lighting conditions found in that sector, provide recommendations and thus achieve better results in the work stations according to light quantity and quality, and energy efficiency. Subsequently, these results will be analyzed based on the Colombian regulations to determine if the companies meet the rules that ensure the employees’ safety and health.